Teachers’ practices during Emergency Remote Teaching: an investigation of the needs for support and the role of Professional Learning Communities - Shauly Anat; Avargil Shirly (Chemistry Teacher International, 2023)
Emergency Remote Teaching (ERT) was implemented during COVID-19 crisis lockdowns. New challenges arose and teachers sought support. Professional Learning Communities (PLCs), where teachers from similar backgrounds meet for learning and discussions, provided one channel of support. The study aimed to better understand PLCs’ role in challenging times. Therefore, we asked: 1. What challenges did teachers face, in addition to pedagogical ones, during ERT? 2. How did the various members of the PLC perceive support as shown by their descriptions of PLC activities? 3. In what ways did the ERT experience shape the teachers’ perceptions of mutual assistance? The research setting was a PLC network for chemistry teachers that met since 2018 face-to-face or via Zoom. PLCs were found important in facing both professional and emotional challenges. Discussions, sharing of teaching materials, and real-time support addressed professional challenges. Having colleagues who faced similar challenges provided support and eased communication. Thus, PLC membership helped teachers face daily challenges and improved their well-being. PLCs are therefore recommended for routine and future hardships. In practice, PLC leaders can use the results to improve teacher relationships. Conclusions add to understanding teacher collaboration in PLCs formed in diverse contexts.